(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
The problem of street children in Africa is a growing concern. Many children in a bid to escape from domestic violence, poverty and appalling living conditions, have turned to the streets in search of better opportunities. These children spend their days and nights living and working on the streets, living in absolute squalor and degrading circumstances. The girls and in some cases, the boys are forced into sexual relationships for protection and food, making them prone to disease and malnutrition. They are often trafficked without education or medical care. Some of them may have no choice; they are abandoned, orphaned, or thrown out of their homes. They live a life of trauma, held captive to their constant cycle of poverty and helplessness, with no hope of a better future; only despair. These children find security and relief from life’s anxieties within their group. By extension, some of these children are on the streets because of mistreatment, neglect and lack of basic necessities of life. As a result, they find ready homes in unoccupied dwellings, uncompleted buildings, market places, under the bridges and wastelands more than their family homes. There are a number of common misconceptions about street children; for example, misconceptions about who they are and why they take to the streets. The focus is on the concept, ‘streetism’, the perception of the society about these street children, their vulnerability and emotional and psychological trauma in Uwem Akpan’s An Ex-Mass Feast (2008), K. Sello Duiker’s Thirteen Cents (2000) and Amma Darko’s Faceless (2003). These works are selected from Nigeria, South Africa and Ghana, respectively, to show that ‘streetism’ is not bound by ethnicity or culture; it is a continental problem. These children are vulnerable, and are at risk of physical, social, emotional and cognitive violations. By allowing their characters especially the female children, to struggle against all odds to live like adults, the selected authors bring to fore, the trauma these homeless and abandoned children go through in the African continent. This paper, hence, concludes that street children should be treated as part of the society, not as destitute.